The Effects of Cinnamon on Metabolic and Hormonal Status of Women With Polycystic Ovary Syndrome: A Randomized Controlled Trial - Sanam Hadipour; Leila Amini; Bahare Afshar; Afsaneh Ghasemi; Hamid Haghani; Homa Sadeghi Avval Shahr; Shayesteh Jahanfar (Journal of Client-centered Nursing Care)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Accordingly, this study investigates the effect of oral capsules of cinnamon extract on the metabolic profile and hormonal status of women with PCOS. Methods: This blinded randomized clinical trial was performed on 66 women with PCOS referred to the gynecology and infertility clinics in Tehran City, Iran from 2016 to 2017. Eligible women were randomly allocated into intervention (n=33) and placebo (n=33) groups. The oral capsule of 3 g cinnamon extract was taken once a day for 12 consecutive weeks by the intervention group and the placebo capsule was given in the same way to the control group. Before and 12 weeks after starting the intervention, blood tests were performed to measure fasting blood sugar (FBS), fasting insulin (FI), triglycerides (TG), total cholesterol, low-density lipoprotein, high-density lipoprotein, total testosterone (TT), and sex hormone binding globulin (SHBG). The student t-test, paired t-test, chi-square test, and analysis of covariance were used to compare groups using the SPSS software, version 16. Meanwhile, P<0.05 were considered significant. Results: Consumption of cinnamon extract only leads to a significant decrease in total TT level compared to placebo (P=0.001), and has no significant effect on FBS, FI, TG, total cholesterol, low-density and high-density lipoprotein cholesterol, SHBG, and free androgen index (FAI). Conclusion: Cinnamon extract at a dose of 3 g/day for 12 consecutive weeks could decrease total TT in women with PCOS, and had no significant effects on metabolic and hormonal indicators in these women. Nevertheless, it is suggested that more studies be conducted with a larger sample size and various doses of cinnamon.